The perception for Good Death of community dwelling Japanese and Thailand respondents - Michiyo Ando; Supawadee Somchit; Mitsunori Miyashita; Laiad Jamjan (JMIR Publications, 2016)
Having a "good death" is a very important goal of palliative care, and it is useful for nurses to understand cultural differences in the perception of a good death to propose nursing care. The purpose of this study was to compare the perception of a "good death" among community-dwelling Japanese and Thai people. Three hundred sixty-nine respondents completed the Good Death Questionnaire. The research design was a cross-sectional study. The scores of the Japanese respondents on "good relationships with medical staff," "being respected as an individual," and "fighting against cancer" were higher among Thai respondents. On the other hand, "environmental comfort," "unawareness of death," "control over the future," and "religious and spiritual comfort" were higher among the Japanese respondents. Among the Japanese, the score for "life completion" was significantly correlated with "role accomplishment and contribution to others." Among the Thai respondents, the score for "good relationships with family" was significantly correlated with "physical and cognitive control." The implications of these results were that Japanese respondents preferred medical treatments, maintaining a good relationship with physicians, and demanding to be respected as an individual. Thai respondent's preferred "environmental comfort" and "religious and spiritual comfort." In the future, medical staff members will need to consider these cultural differences when proposing nursing care.